EFEK ANTI INFLAMASI IN VITRO EKSTRAK ETANOL DAUN KARET KEBO (Ficus elastica) DENGAN METODE STABILISASI MEMBRAN Red Blood Cell (RBCs) - Suhaenah, Asriani; Widiastuti, Harti; Aprianti, Tiara (Fakultas Farmasi UMI, 2025)
The rubber kebo plant (Ficus elastica) is traditionally known to have various benefits, including as an anti-inflammatory agent. This study aimed to evaluate the anti-inflammatory effect of ethanol extract of rubber kebo leaves using the red blood cell (RBCs) membrane stabilisation method in vitro. Kebo rubber leaves were extracted by a maceration method using 96% ethanol, and anti-inflammatory activity was tested by measuring the stability of RBCs membrane against hypotonic solution-induced haemolysis. The results showed that ethanol extract of rubber kebo leaves had anti-inflammatory activity with a percentage of membrane stabilisation of 31.156% at a concentration of 40 ppm and reached 51.998% at a concentration of 200 ppm. This activity is caused by the content of secondary metabolites such as flavonoids and tannins that work by stabilising the red blood cell membrane. Compared to the positive control of diclofenate sodium, the extract showed competitive effectiveness, albeit lower